Pengembangan Bahan Ajar untuk Konten Learning Management System MOODLE bagi MGMP Matematika SMP Kabupaten Tasikmalaya - Mulyani, Eva; Prabawati, Mega Nur; Yulianto, Eko; Mansyur, M. Zulfikar (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2024)
Moodle is one of the most popular and frequently used LMS in the world of education. This research aims to increase the understanding of junior high school mathematics teachers in the Sukaraja area, Tasikmalaya Regency regarding the development of teaching materials for the MOODLE Learning Management System Content, so that they can utilize this technology to improve the quality of learning and student learning outcomes. The method used is a classical and individual approach. Based on the results of the analysis, it was concluded that the training increased understanding of the use of Moodle LMS in mathematics education, enabling participants to develop interactive teaching materials. Collaboration between Mathematics teachers at MGMP is encouraged, facilitating knowledge exchange. Technology and appropriate instructional design improve mathematics learning in middle school with access to diverse materials and interesting ways of learning.